STUDI EKSPERIMEN PERPINDAHAN PANAS KONVEKSI PAKSA EKSTERNAL PADA PLAT DATAR - Rijalulakbar Dewantoro; Arrad Ghani Safitra; Lohdy Diana (PROSIDING SNAST, 2018)
Heat transfer is divided into three, conduction, convection and radiation. Convection is the heat transfer due to bulk movement within fluids. Force convection that happen on the surface of the object is the case of heat transfer for external flow. Force convection declared by the value of convection coefficient (h).Convection coefficient its affected by geometry of the object, fluid velocity, and the value of heat flux. The research has been done by experiment using flat plate aluminum with length 0,275m, width 0,065m and height 0,008m. The goal of this experiment is to know the characteristic of external force convection on flat plate. The object is heated by electric heater under the object, then its cooled by the air from centrifugal blower. Variation of fluid velocity and heat flux was performed to the object. Data retrieval using thermistor (temperature sensor) that integrated with arduino, multimeter (voltage and current sensor), and anemometer (fluid velocity sensor). During experiment, the data taken are surface temperature and fluid velocity. From the experimental result obtained the best value of convection coefficient located on 0,005m, that is the variation fluid velocity 4,8 m/s the value is 275,4 W/m2K. This shows that the higher the fluid velocity will increase the value of the convection coefficient.